Preventing student brawls through integration of character education values in social studies subjects - Khodijah, Isah Siti; Wasino, Wasino; Sunarto, Sunarto (Universitas Negeri Semarang, 2024)
The cases of student brawls at school in Indramayu occur almost every year. Therefore, this study aimed to analyze the factors that cause school efforts to prevent by integrating character education values in social studies subjects. The approach was qualitative with the type of case study research, data sources obtained from informants selected using purposive sampling through observation, interviews, and document studies. The location taken was at SMPN 1 Sliyeg and MTsN 3 Indramayu. The results showed that the factors that cause student brawls include the influence of the family environment, peers, and the school environment. School efforts to prevent brawls were carried out through the socialization of character education, which manifested in the form of school programs integrated into social studies subjects and the habituation of character integrity. Efforts to incorporate the value of character education in social studies subjects were carried out through a holistic approach, beginning with planning, implementation, and evaluation. The effort was analyzed using Talcott Parsons' AGIL theory. Based on the results of the study, the value of character education is a school strategy through integration in the program in social studies subjects to prevent continuous brawls by integrating character education to generate good citizens.